Ancient viral integrations in marsupials: a potential antiviral defence. Issue 2 (2nd September 2021) - Harding, Emma F; Russo, Alice G; Yan, Grace J H; Waters, Paul D; White, Peter A
Abstract: Marsupial viruses are understudied compared to their eutherian mammal counterparts, although they may pose severe threats to vulnerable marsupial populations. Genomic viral integrations, termed 'endogenous viral elements' (EVEs), could protect the host from infection. It is widely known past viral infections and EVEs play an active role in antiviral defence in invertebrates and plants. This study aimed to characterise actively transcribed EVEs in Australian marsupial species, because they may play an integral role in cellular defence against viruses. This study screened publicly available RNA sequencing data sets ( n = 35) and characterised 200 viral transcripts from thirteen Australian marsupial species. Of the 200 transcripts, 188 originated from either Bornaviridae, Filoviridae, or Parvoviridae EVEs. The other twelve transcripts were from putative active infections from members of the Herpesviridae and Anelloviridae, and Hepadnaviridae . EVE transcripts ( n = 188) were mapped to marsupial genomes (where available, n = 5/13) to identify the genomic insertion sites. Of the 188 transcripts, 117 mapped to 39 EVEs within the koala, bare-nosed wombat, tammar wallaby, brushtail possum, and Tasmanian devil genomes. The remaining eight animals had no available genome (transcripts n = 71). Every marsupial has Bornaviridae, Filoviridae, and Parvoviridae EVEs, a trend widely observed in eutherian mammals. Whilst eutherian bornavirus EVEs are predominantly nucleoprotein-derived, marsupial bornavirus EVEs demonstrate a surprising replicase gene bias. We predicted these widely distributed EVEs were conserved within marsupials from ancient germline integrations, as many were over 65 million years old. One bornavirus replicase EVE, present in six marsupial genomes, was estimated to be 160 million years old, predating the American–Australian marsupial split. We considered transcription of these EVEs through small non-coding RNA as an ancient viral defence. Consistent with this, in koala small RNA sequence data sets, we detected Bornaviridae replicase and Filoviridae nucleoprotein produced small RNA. These were enriched in testis tissue, suggesting they could protect marsupials from vertically transmitted viral integrations.